High-capacity and high-rate sodium vanadium phosphate positive electrode material and preparation method thereof
By adopting two-site co-doping technology in the sodium vanadium phosphate positive electrode material and introducing specific metal ions, the problem of low capacity retention at high magnifications of existing materials is solved, and a higher discharge specific capacity and energy density are achieved.
Patent Information
- Application Number
- CN202411341789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing vanadium sodium phosphate positive electrode materials have relatively small content in the 2.5-4.0V charge and discharge interval, low energy density, and at high magnification, there are problems such as large polarization voltage, low specific capacity and capacity retention.
The chemical formula of Na3-xMxV2-yNy(PO4)3 is formed by introducing a combination of K and Li or one of them into the sodium vanadium phosphate positive electrode material, as well as doping metal ions such as Mn, Fe, Co, and Ni, thereby improving the valence mixed state and structural stability of vanadium ions.
Higher discharge specific capacity and energy density in the voltage range of 2.5-4.0V is achieved, and better capacity retention and structural stability are maintained at high magnifications.
Smart Images

Figure CN119601653A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and particularly relates to a sodium vanadium phosphate cathode material with high capacity and rate and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have been widely used at present. However, considering the relatively high price of lithium, the demand for developing a new sodium-ion secondary battery system by using sodium, which has similar properties, more abundant reserves and lower price, instead of lithium is becoming stronger. Improving the discharge capacity of the cathode, increasing the discharge voltage platform and enhancing the capacity retention rate after cycling can effectively improve the performance of current sodium-ion batteries. The sodium-ion conductor sodium vanadium phosphate cathode material is a potential cathode material for sodium-ion batteries. It has a relatively stable structural framework to provide good capacity retention rate and material safety. The metal vanadium cations therein provide battery capacity through redox reactions, with good reversibility and can be used for a long time. However, the current sodium vanadium phosphate cathode materials still have the following problems:
[0003] (1) In the charge-discharge range of 2.5 - 4.0 V, the redox reaction of vanadium ions only involves the transformation from V3+ to V4+, providing less capacity, and only a voltage platform of about 3.5 V can appear during the charge-discharge process, resulting in a lower energy density.
[0004] (2) At a rate of 20C, with the rapid insertion and removal of sodium ions, the sodium vanadium phosphate cathode material shows characteristics of large polarization voltage, low specific capacity and low capacity retention rate, and is not well suitable for high-rate charge-discharge situations. Summary of the Invention
[0005] Embodiments of the present application are proposed to make up for the deficiencies of the prior art, and provide a sodium vanadium phosphate cathode material with high capacity and rate and a preparation method thereof to solve the problems existing in the prior art.
[0006] To solve the above technical problems, the present invention provides the following technical solutions:
[0007] A sodium vanadium phosphate cathode material with high capacity and rate, whose chemical formula is Na 3-x M x V 2-y N y (PO4)3, where the value range of x in the chemical formula is 0 < x ≤ 0.4, the value range of y is 0 < y ≤ 0.8, M is a combination of K and Li or one of them, and N is a combination of one or more of Mn, Fe, Co, Ni.
[0008] A preparation method of a sodium vanadium phosphate cathode material with high capacity and rate, comprising the following steps:
[0009] S01: dissolving lithium, sodium, potassium, vanadium, manganese, iron, cobalt, nickel compounds, phosphates and reducing chelating acids such as citric acid in deionized water in proportion to obtain a clear solution;
[0010] S02: heating the solution obtained in S01 in a water bath at 80 degrees Celsius to allow the acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel;
[0011] S03: drying the gel obtained in S02 under vacuum at 120 degrees Celsius to obtain a solid, and grinding it into powder;
[0012] S04: The powder obtained in S03 is pre-baked at 350 degrees Celsius to obtain a black powder, which is fully ground and placed in an alumina crucible. It is sintered at 800 degrees Celsius in a nitrogen atmosphere, and the co-doped sodium vanadium phosphate positive electrode material is obtained by naturally cooling.
[0013] As a further technical solution of the present invention: the molar ratio of the acid to the metal ion in step S01 is in the range of 0.5:1 to 4:1.
[0014] As a further technical solution of the present invention: stirring in step S02 for 2-4 hours.
[0015] As a further technical solution of the present invention: the pre-baking time in step S03 is 2-8 hours, and the high-temperature sintering time is 4-16 hours.
[0016] As a further technical solution of the present invention: the soluble substances of lithium, sodium and potassium in step S01 are one or more mixtures of hydroxide, carbonate, bicarbonate, acetate, nitrate and phosphate.
[0017] As a further technical solution of the present invention: the salts of manganese, iron, cobalt and nickel in step S01 are carbonates, sulfates, acetates, oxalates, nitrates, acetylacetonates, phosphates or one or more mixtures of oxides, peroxides, hydroxides and hydroxy oxides.
[0018] As a further technical solution of the present invention: the vanadium source in step S01 is ammonium metavanadate, vanadium pentoxide, sodium metavanadate, sodium pyrovanadate or vanadium hydroxide.
[0019] As a further technical solution of the present invention: in step S01, the phosphorus source is ammonium dihydrogen phosphate, sodium dihydrogen phosphate, sodium hydrogen phosphate or ammonium hydrogen phosphate.
[0020] As a further technical solution of the present invention: in step S01, the reducing chelating acid is oxalic acid, citric acid or hydrated citric acid.
[0021] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0022] 1. The method of achieving high-capacity sodium vanadium phosphate positive electrode material by dual-site co-doping has achieved higher discharge specific capacity and energy density in the voltage range of 2.5-4.0V. This can be attributed to the valence mixing of vanadium ions caused by low-valent doping of metal ions, which stimulates the transformation of vanadium ions from V4+ to V5+ at a new reversible charge and discharge platform at 3.8V in this range. At the same time, the redox of nickel, manganese and other ions themselves also participates in the charge and discharge process, allowing more sodium ions to migrate.
[0023] 2. The dual-site co-doping prepared by the present invention realizes a high-capacity sodium vanadium phosphate positive electrode material with better structural stability. The incorporation of larger radius ions into the crystal increases the unit cell volume and acts as supporting ions, thereby reducing the irreversible structural damage caused by phase change, improving the specific capacity at high rate and obtaining a better capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a powder X-ray diffraction comparison diagram of the co-doped sodium vanadium phosphate positive electrode material and the sodium vanadium phosphate positive electrode material in Example 1.
[0025] Figure 2 This is a first cycle charge and discharge curve diagram of the co-doped sodium vanadium phosphate positive electrode material and the sodium vanadium phosphate positive electrode material in Example 1 at 0.1C in the voltage range of 2.5-4.0V.
[0026] Figure 3 This is a cycle curve diagram of the co-doped sodium vanadium phosphate positive electrode material and the sodium vanadium phosphate positive electrode material in Example 1 at 20C in the voltage range of 2.5-4.0V.
[0027] Figure 4 It is a variable charge rate cycle curve diagram of the co-doped sodium vanadium phosphate positive electrode material and the sodium vanadium phosphate positive electrode material in Example 1 within the voltage range of 2.5-4.0V.
[0028] In the figure, the charge and discharge rates are 0.1C, 0.5C, 1C, 2C, 5C, 10C, 20C, and 0.1C, respectively, and each charge and discharge cycle is 10 cycles.
[0029] Wherein NVP is sodium vanadium phosphate positive electrode material, and NVMP is the co-doped sodium vanadium phosphate positive electrode material in Example 1. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Reference Figure 1-4 A high-capacity and high-rate sodium vanadium phosphate cathode material and a preparation method thereof, with the chemical formula Na3-xMxV2-yNy(PO4)3, characterized in that the value range of x in the chemical formula is 0 < x ≤ 0.4, the value range of y is 0 < y ≤ 0.8, M is a combination of K and Li or one of them, and N is a combination of one or more of Mn, Fe, Co, and Ni.
[0032] Meanwhile, the present invention also provides a preparation method of a high-capacity and high-rate sodium vanadium phosphate cathode material, and the preparation method includes the following steps:
[0033] S01: Dissolve soluble substances of lithium, sodium, and potassium, iron compounds, vanadium sources, and reducing chelating acids in deionized water in proportion to obtain a clear solution;
[0034] S02: Water bath heat and stir the solution obtained in S01 at 80 °C for 2-4 h to allow the acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel;
[0035] S03: Vacuum dry the gel obtained in S02 at 120 °C to obtain a solid, and grind it into powder;
[0036] S04: Pre-calcine the powder obtained in S03 at 350 °C for 2-8 h to obtain a black powder. After fully grinding, place it in an alumina crucible, and sinter it at 800 °C for 4-16 h under a nitrogen atmosphere, and naturally cool to obtain the co-doped sodium vanadium phosphate cathode material.
[0037] Furthermore, in S01, the molar ratio of the acid to the metal ions ranges from 0.5:1 to 4:1.
[0038] Still further, in S01, the soluble substances of lithium, sodium, and potassium are one or more mixtures of hydroxides, carbonates, bicarbonates, acetates, nitrates, and phosphates.
[0039] Still further, in S01, the iron compounds are one or more mixtures of carbonates, sulfates, acetates, oxalates, nitrates, acetylacetonates, phosphates, or oxides, peroxides, hydroxides, and oxyhydroxides.
[0040] Still further, in S01, the vanadium source is ammonium metavanadate, vanadium pentoxide, sodium metavanadate, sodium pyrophosphate, vanadium hydroxide, and other vanadates.
[0041] Still further, in S01, the reducing chelating acid is citric acid or hydrated citric acid, oxalic acid, etc.
[0042] Specifically, the present invention provides the following multiple groups of examples:
[0043] Embodiment 1:
[0044] Preparation of co-doped sodium vanadium phosphate cathode material Na by sol-gel method 2.9 K 0.1 V 1.8 Mn 0.1 Fe 0.1 The (PO4)3 process includes the following steps:
[0045] S01: Dissolve oxalic acid (0.002 mol), sodium metavanadate (0.0036 mol), diammonium phosphate (0.0060 mol), sodium hydroxide (0.0004 mol), potassium hydroxide (0.0002 mol), ferrous oxalate dihydrate (0.0002 mol), and manganese oxalate (0.0002 mol) in 60 mL of deionized water in sequence to obtain a clear solution.
[0046] S02: The solution obtained in S01 is heated in a water bath at 80 degrees Celsius and stirred for 2-4 hours to allow the citric acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel;
[0047] S03: drying the gel obtained in S02 under vacuum at 120 degrees Celsius to obtain a solid, and grinding it into powder;
[0048] S04: The powder obtained in S03 was pre-baked at 350 degrees Celsius for 2 hours to obtain a black powder. After being fully ground, it was placed in an alumina crucible and sintered at 800 degrees Celsius for 10 hours in a nitrogen atmosphere. The co-doped sodium vanadium phosphate positive electrode material Na 2.9 K 0.1 V 1.8 Mn 0.1 Fe 0.1 (PO4)3.
[0049] The co-doped sodium vanadium phosphate positive electrode material prepared in the example, the conductive agent acetylene black, and the binder PVDF were mixed into a slurry in a mass ratio of 8:1:1 and then coated to form a positive electrode sheet. The constant rate charge and discharge test was carried out at a rate of 0.1C in the voltage range of 2.5-4.0V, and its initial discharge capacity was 114mAh / g. At 20C, its discharge capacity was 86mAh / g, still maintaining 75% of the 0.1C discharge. After 1000 cycles at 20C, the capacity retention rate was 94%.
[0050] Embodiment 2:
[0051] Preparation of co-doped sodium vanadium phosphate cathode material Na by sol-gel method 2.8 K 0.15 L i 0.05 The V2(PO4)3 process includes the following steps:
[0052] S01: Dissolve citric acid monohydrate (0.004 mol), ammonium metavanadate (0.004 mol), ammonium dihydrogen phosphate (0.006 mol), anhydrous sodium carbonate (0.0028 mol), anhydrous potassium carbonate (0.00015 mol), and lithium carbonate (0.00005 mol) in 60 mL of deionized water in sequence to obtain a clear solution;
[0053] S02: The solution obtained in S01 is heated in a water bath at 80 degrees Celsius and stirred for 2-4 hours to allow the citric acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel;
[0054] S03: drying the gel obtained in S02 under vacuum at 120 degrees Celsius to obtain a solid, and grinding it into powder;
[0055] S04: The powder obtained in S03 was pre-baked at 350 degrees Celsius for 3 hours to obtain a black powder. After being fully ground, it was placed in an alumina crucible and sintered at 800 degrees Celsius for 8 hours in a nitrogen atmosphere. The co-doped sodium vanadium phosphate positive electrode material Na 2.8 K 0.15 Li 0.05 V2(PO4)3.
[0056] The co-doped sodium vanadium phosphate positive electrode material prepared in the example was mixed with the conductive agent acetylene black and the binder PVDF in a mass ratio of 8:1:1 to form a slurry and then coated to form a positive electrode sheet. The constant rate charge and discharge test was carried out at a rate of 0.1C in the voltage range of 2.5-4.0V, and the first cycle discharge capacity was 102mAh / g. At 20C, the first cycle discharge capacity was 20mAh / g.
[0057] Embodiment 3:
[0058] Preparation of co-doped sodium vanadium phosphate cathode material Na by sol-gel method 2.8 K 0.2 V 1.8 Mn 0.15 Fe 0.05 The (PO4)3 process includes the following steps:
[0059] S01: Oxalic acid (0.008 mol), sodium metavanadate (0.0036 mol), ammonium dihydrogen phosphate (0.0060 mol), sodium acetate (0.0002 mol), potassium acetate (0.0004 mol), ferric oxalate pentahydrate (0.0001 mol), and manganese acetate tetrahydrate (0.0003 mol) were dissolved in 60 mL of deionized water in sequence to obtain a clear solution.
[0060] S02: The solution obtained in S01 is heated in a water bath at 80 degrees Celsius and stirred for 2-4 hours to allow the citric acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel;
[0061] S03: drying the gel obtained in S02 under vacuum at 120 degrees Celsius to obtain a solid, and grinding it into powder;
[0062] S04: The powder obtained in S03 was pre-baked at 350 degrees Celsius for 6 hours to obtain a black powder. After being fully ground, it was placed in an alumina crucible and sintered at 800 degrees Celsius for 10 hours in a nitrogen atmosphere. The co-doped sodium vanadium phosphate positive electrode material Na 2.8 K 0.2 V 1.8 Mn 0.15 Fe 0.05( PO4)3.
[0063] The prepared co-doped sodium vanadium phosphate positive electrode material, conductive agent acetylene black, and binder PVDF were mixed into a slurry in a mass ratio of 8:1:1 and then coated to form a positive electrode sheet. The constant rate charge and discharge test was carried out at a rate of 0.1C in the voltage range of 2.5-4.0V, and its discharge capacity was 107mAh / g; at 20C, its discharge capacity was 85mAh / g, and the capacity retention rate after 1000 cycles was 94%.
[0064] Embodiment 4:
[0065] Preparation of co-doped sodium vanadium phosphate cathode material Na by sol-gel method 2.6 K 0.4 V 1.8 Mn 0.1 Ni 0.1 The (PO4)3 process includes the following steps:
[0066] S01: Dissolve citric acid monohydrate (0.020 mol), ammonium metavanadate (0.0036 mol), ammonium dihydrogen phosphate (0.0060 mol), sodium hydroxide (0.0052 mol), potassium hydroxide (0.0008 mol), nickel hydroxide (0.0002 mol), and manganese acetate tetrahydrate (0.0002 mol) in 60 mL of deionized water in sequence to obtain a clear solution.
[0067] S02: The solution obtained in S01 is heated in a water bath at 80 degrees Celsius and stirred for 2-4 hours to allow the citric acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel;
[0068] S03: drying the gel obtained in S02 under vacuum at 120 degrees Celsius to obtain a solid, and grinding it into powder;
[0069] S04: The powder obtained in S03 was pre-baked at 350 degrees Celsius for 8 hours to obtain a black powder. After being fully ground, it was placed in an alumina crucible and sintered at 800 degrees Celsius for 16 hours in a nitrogen atmosphere. The co-doped sodium vanadium phosphate positive electrode material Na 2.6 K 0.4 V 1.8 Mn 0.1 Ni 0.1 (PO4)3.
[0070] The co-doped sodium vanadium phosphate positive electrode material prepared in the example, the conductive agent acetylene black, and the binder PVDF were mixed into a slurry in a mass ratio of 8:1:1 and then coated to form a positive electrode sheet. The constant rate charge and discharge test was carried out at a rate of 0.1C in the voltage range of 2.5-4.0V, and its initial discharge capacity was 110mAh / g. At 20C, its discharge capacity was 70mAh / g, and after 1000 cycles at 20C, the capacity retention rate was 90%.
[0071] Embodiment 5:
[0072] Preparation of co-doped sodium vanadium phosphate cathode material Na by sol-gel method 2.7 K 0.3 V 1.8 Mn 0.1 Co 0.1 The (PO4)3 process includes the following steps:
[0073] S01: Dissolve oxalic acid (0.024 mol), ammonium metavanadate (0.0036 mol), diammonium phosphate (0.0060 mol), anhydrous sodium carbonate (0.0027 mol), anhydrous potassium carbonate (0.0003 mol), cobalt hydroxide (0.0002 mol), and manganese oxalate (0.0002 mol) in 60 mL of deionized water in sequence to obtain a clear solution.
[0074] S02: The solution obtained in S01 is heated in a water bath at 80 degrees Celsius and stirred for 2-4 hours to allow the citric acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel;
[0075] S03: drying the gel obtained in S02 under vacuum at 120 degrees Celsius to obtain a solid, and grinding it into powder;
[0076] S04: The powder obtained in S03 was pre-baked at 350 degrees Celsius for 8 hours to obtain a black powder. After being fully ground, it was placed in an alumina crucible and sintered at 800 degrees Celsius for 16 hours in a nitrogen atmosphere. The co-doped sodium vanadium phosphate positive electrode material Na 2.7 K 0.3 V 1.8 Mn 0.1Co 0.1 (PO4)3.
[0077] The co-doped sodium vanadium phosphate positive electrode material prepared in the example, the conductive agent acetylene black, and the binder PVDF were mixed into a slurry in a mass ratio of 8:1:1 and then coated to form a positive electrode sheet. The constant rate charge and discharge test was carried out at a rate of 0.1C in the voltage range of 2.5-4.0V, and its initial discharge capacity was 108mAh / g. At 20C, its discharge capacity was 75mAh / g, and after 1000 cycles at 20C, the capacity retention rate was 92%.
[0078] In summary, the sodium vanadium phosphate positive electrode material Na3V2(PO4)3 synthesized by a similar method in the present invention has a discharge capacity of only 103 mAh / g at 0.1C in the voltage range of 2.0-4.5 V; the discharge capacity at 20C is 40 mAh / g, which only retains 39% of the discharge capacity at 0.1C. After 1000 cycles at 20C, the capacity retention rate is only 62%.
[0079] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0080] In addition, it should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment have also been appropriately combined to form other implementation modes that are easy for those skilled in the art to understand.
Claims
1. A sodium vanadium phosphate positive electrode material with high capacity and rate, characterized in that: Its chemical formula is Na 3-x M x V 2-y N y (PO4)3, wherein the value range of x in the chemical formula is 0 < x ≤ 0.4, the value range of y is 0 < y ≤ 0.8, M is a combination of K and Li or one of them, and N is a combination of one or more of Mn, Fe, Co, and Ni.
2. A method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate, characterized in that: The following steps are involved: S01: dissolving lithium, sodium, potassium, vanadium, manganese, iron, cobalt, nickel compounds, phosphate and reducing chelating acid in deionized water in proportion to obtain a clear solution; S02: heating the solution obtained in S01 in a water bath at 80 degrees Celsius to allow the acid and metal ions to fully undergo hydrolysis and condensation reactions to obtain a gel; S03: drying the gel obtained in S02 under vacuum at 120 degrees Celsius to obtain a solid, and grinding it into powder; S04: The powder obtained in S03 is pre-baked at 350 degrees Celsius to obtain a black powder, which is fully ground and placed in an alumina crucible. It is sintered at 800 degrees Celsius in a nitrogen atmosphere, and the co-doped sodium vanadium phosphate positive electrode material is obtained by naturally cooling.
3. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: The molar ratio of the acid to the metal ion in step S01 is in the range of 0.5:1 to 6:
1.
4. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: The stirring time in step S02 is 2-4h.
5. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: The pre-baking time in step S03 is 2-8 hours, and the high-temperature sintering time is 4-16 hours.
6. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: The soluble substances of lithium, sodium and potassium in step S01 are a mixture of one or more of hydroxide, carbonate, bicarbonate, acetate, nitrate and phosphate.
7. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: The salts of manganese, iron, cobalt and nickel in step S01 are carbonates, sulfates, acetates, oxalates, nitrates, acetylacetonates, phosphates or mixtures of one or more of oxides, peroxides, hydroxides and oxyhydroxyls.
8. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: The vanadium source in step S01 is ammonium metavanadate, vanadium pentoxide, sodium metavanadate, sodium pyrovanadate or vanadium hydroxide.
9. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: In step S01, the phosphorus source is ammonium dihydrogen phosphate, sodium dihydrogen phosphate, sodium hydrogen phosphate or ammonium hydrogen phosphate.
10. The method for preparing a sodium vanadium phosphate positive electrode material with high capacity and rate according to claim 2, characterized in that: In step S01, the reducing chelating acid is citric acid or hydrated citric acid or oxalic acid.
Citation Information
Patent Citations
Method for preparing multi-stage spherical sodium vanadium phosphate composite positive electrode material
CN108807899A
Double-site doped modified sodium vanadium phosphate positive electrode material as well as preparation method and application thereof
CN114156453A
Vanadium-doped sodium vanadium phosphate / carbon composite material as well as preparation and use methods thereof
CN116190584A
Vanadium sodium phosphate positive electrode material, sodium ion battery, preparation method therefor, and use thereof
US20210167387A1